Digital Precoders for Partially Spectral Overlapping Subarrays in mmWave Satellite Communications - Hsiao, Feng-Chin; Ku, Meng-Lin; Song, Yan-Zhou (IEEE access, 2024)
With the emergence of sixth-generation (6G) wireless services, low Earth orbit (LEO) satellite communications are increasingly recognized as a promising solution for providing extensive wireless coverage to terrestrial users. Subarray-based hybrid beamforming offers an efficient implementation method in millimeter wave (mmWave) communications; however, current approaches that use either non-overlapping or fully overlapping spectrum for subarrays may result in inefficient spectrum usage or severe inter-beam interference. In this paper, we investigate digital precoders for two partially spectral overlapping subarrays of LEO satellites using hybrid beamforming to enhance spectrum utilization while mitigating inter-beam interference. We propose and analyze an interference model for partially spectral overlapping subarrays, which theoretically characterizes the inter-beam interference effect resulting from partial spectrum overlapping in hybrid beamforming. Utilizing an approximated interference model to simplify the analysis, we derive a closed-form expression for a minimum mean square error (MMSE)-based digital precoder, constrained by total transmit power. Extensive computer simulations demonstrate the effectiveness of the proposed MMSE digital precoder in improving the bit error rate (BER), signal-to-interference-plus-noise ratio (SINR), sum rate, and spectrum utilization.